Discrepancy in the Identification of the Atlantic/Pacific Front in the Central Arctic Ocean: NO Versus Nutrient Relationships. Issue 7 (1st April 2019) - Alkire, Matthew B.; Rember, Robert; Polyakov, Igor
Abstract: Fronts in the NO parameter, a semiconservative tracer combining nitrate and dissolved oxygen, and dynamic height were observed in the central East Siberian Sea that distinguished Atlantic and Pacific contributions to the upper halocline of the Amerasian Basin during the summer of 2015. The NO front was aligned with the Transpolar Drift, and its position over the Mendeleyev Ridge indicates that Pacific waters were generally restricted to the Canada Basin and did not spread to the central Arctic. This interpretation lies in contrast to the distribution of Pacific water fractions, calculated using established relationships between nitrate and phosphate, and indicates that traditional tracers used to quantify Pacific water contributions to the Arctic Ocean are no longer accurate. Key Points: The NO parameter was used to separate upper halocline waters originating on the Chukchi versus East Siberian Sea shelves Traditional methods of identifying and separating Pacific from Atlantic waters in the central Arctic may no longer be reliable Pacific water was generally restricted to the Canadian Basin side of the Mendeleyev Ridge during summer 2015